Development and Improvement of Operational Reliability of Gas Transportation System Facilities as Power Security Factor of the Republic of Belarus - P. P. Piotukh (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The problems pertaining to the complex diagnostics of gas pipeline equipment operated by BELTRANSGAZ enterprise are considered in the paper. The importance of the matter is justified by the necessity of the stable and reliable power supply as to individual enterprises so to some entire branches of economy. This purpose may be reached only through trouble-free and safety operation of gas transportation facilities.